2019
DOI: 10.3390/sym11060758
|View full text |Cite
|
Sign up to set email alerts
|

On Nonlinear Reaction-Diffusion Model with Time Delay on Hexagonal Lattice

Abstract: In the work, a nonlinear reaction-diffusion model in a class of delayed differential equations on the hexagonal lattice is considered. The system includes a spatial operator of diffusion between hexagonal pixels. The main results deal with the qualitative investigation of the model. The conditions of global asymptotic stability, which are based on the Lyapunov function construction, are obtained. An estimate of the upper bound of time delay, which enables stability, is presented. The numerical study is execute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The dynamics of such type systems in a general case is studied in [ 16 ]. Some of our previous results were also related to their behavior [ 17 , 18 , 19 ]. In the next section, we will consider one simple case allowing us to develop the method of parameter identification for the model such as (24).…”
Section: Methodsmentioning
confidence: 90%
“…The dynamics of such type systems in a general case is studied in [ 16 ]. Some of our previous results were also related to their behavior [ 17 , 18 , 19 ]. In the next section, we will consider one simple case allowing us to develop the method of parameter identification for the model such as (24).…”
Section: Methodsmentioning
confidence: 90%
“…For this purpose, linearization methods and the direct method of lyapunay were used. At the same time, the model of interaction of subpopulations in the case of the spread of several virus strains and the question of nonlinear analysis of such models are of considerable interest [5][6][7][8].…”
Section: медична інформатика медична інформатика та інженеріяmentioning
confidence: 99%
“…It was shown that they depend on the value of delay τ. In [10], the corresponding model was constructed in the case of a three-dimensional array (or hexagonal lattice) of immunopixels, for which the global asymptotic stability was investigated. In both cases, we evidenced the dependence of phase portraits on τ.…”
Section: Modeling Antibody-antigen Interaction With the Help Of Diffementioning
confidence: 99%
“…In the works [9,10], the model of immunosensors is offered in the class of differential equations for both square and hexagonal lattices. In [9], the conditions of the local asymptotic stability were proposed, and qualitative behavior was analyzed.…”
Section: Introductionmentioning
confidence: 99%